Physical exercise regulates apoptosis and prostatic inflammatory effects induced by high-fat diet in PPAR-alpha deleted mice - Tavares, Maria Eduarda Almeida [UNESP]; Veras, Allice Santos Cruz [UNESP]; Thorpe, Hayley Hope Allyssa; Baptista, Danilo Bianchini [UNESP]; Teixeira, Giovana Rampazzo [UNESP] (Elsevier, 2022)
The high-fat diet (HFD) promotes obesity and develops inflammation, causing dysregulation of energy metabolism and prostatic neoplastic tissue changes. PPARɑ deletion leads to loss of homeostasis between the pro and anti-inflammatory response, and dysregulation of lipid metabolism, causing changes in different physiological processes and damage to the prostate. On the other hand, aerobic physical exercise has been suggested as a non-pharmacological tool to improve energy metabolism and cellular metabolism in the prostate, however, the underlying molecular mechanism remains unclear. the current study aimed to evaluate PPARα as a possible regulator of the protective effects of aerobic physical exercise in the prostate by examining prostatic alterations in wild-type and PPARα deletion mice fed a standard diet or an HFD. Wild-type and PPARα-null mice were fed a standard or HFD diet for 12 weeks, and submitted to aerobic physical exercise for 8 weeks. The HFD promoted the increase of inflammatory markers IL-6, TNF-α, NF-kB, and an increase of inflammatory foci in animals in both genotypes. Although the PPARα deletion animals submitted to the aerobic physical exercise were not able to regulate response pro-inflammatory, but promoted an increase in IL-10 in the prostate. In animals WT, the aerobic physical exercise, reduced all inflammatory markers, improve the inflammatory response, and showed a higher expression of BAX and IL-10 proteins was protective against prostatic tissue lesions. Suggested that PPARα deletion associated with HFD suppressed apoptosis and increased damage prostate. On other hand, aerobic physical exercise improves prostatic tissue by increasing the response to anti-inflammatory and apoptosis protein.
Keywords: Apoptosis; Histopathology prostatic; Inflammation; Peroxisome proliferator-activated receptor α; Physical exercise